Study the Negative Effects of Pseudoephedrine on Brain Tissues in Adult Albino Male Rats - Raghad Hazem Hamad Al-Abbasi; Muneef Saab Ahmad Al-Janabi; Iyad Hamid Ibrahim (Indian Journal of Forensic Medicine & Toxicology, 2021)
In this study, (24) male animals were used, which were divided randomly into four groups. Each groupincluded (6) animals, which are: the control group that was given drinking water and food daily, and thegroup of rats treated with pseudoephedrine at a dose of (40) mg / Kg of body weight for a period of (30)days, the group of rats treated with pseudoephedrine at a dose of (40) mg / kg of body weight for a periodof (40) days, the group of rats treated with pseudoephedrine at a dose of (40) mg / kg of body weight for aperiod of (50) days, the animals dosed the drug by the oropharyngeal tube at a dose of (1) ml, and after theend of the experiment, the animals were scarified , brain samples were taken and preserved with formalinat a concentration of 10% until the tissue sections were made, when the meningeal membrane appeared theupper layers of the cerebral cortex in the group treated with pseudoephedrine for a period of 30 days wereclose to normal, while the group treated with pseudoephedrine for a period of (40) days showed shrinkagein the deep layers of the cerebral cortex and hemolysis in many blood vessels, and the meningeal membraneappeared.